Enzymatic Synthesis and Antimicrobial Activity of Oligomer Analogues of Medicinal Biopolymers from Comfrey and Other Species of the Boraginaceae Family - Maia Merlani; Dieter M. Scheibel; Vakhtang Barbakadze; Lali Gogilashvili; Lela Amiranashvili; Athina Geronikaki; Valentina Catania; Domenico Schillaci; Giuseppe Gallo; Ivan Gitsov (MDPI AG, 2022)
This study reports the first enzymatic synthesis leading to several oligomer analogues of poly[3-(3,4-dihydroxyphenyl)glyceric acid]. This biopolymer, extracted from plants of the Boraginaceae family has shown a wide spectrum of pharmacological properties, including antimicrobial activity. Enzymatic ring opening polymerization of 2-methoxycarbonyl-3-(3,4-dibenzyloxyphenyl)oxirane (MDBPO) using lipase from Candida rugosa leads to formation of poly[2-methoxycarbonyl-3-(3,4-dibenzyloxyphenyl)oxirane] (PMDBPO), with a degree of polymerization up to 5. Catalytic debenzylation of PMDBPO using H2 on Pd/C yields poly[2-methoxycarbonyl-3-(3,4-dihydroxyphenyl)oxirane] (PMDHPO) without loss in molecular mass. Antibacterial assessment of natural polyethers from different species of Boraginaceae family Symhytum asperum, S. caucasicum,S. grandiflorum, Anchusa italica, Cynoglossum officinale, and synthetic polymers, poly[2-methoxycarbonyl-3-(3,4-dimethoxyphenyl)oxirane (PMDMPO) and PMDHPO, reveals that only the synthetic analogue produced in this study (PMDHPO) exhibits a promising antimicrobial activity against pathogenic strains S.aureus ATCC 25923 and E.coli ATCC 25922 the minimum inhibitory concentration (MIC) being 100 µg/mL.